Development of Web Application-Based Learning Model for TOEFL Learning - Agustinus Prasetyo Edy Wibowo (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
This research aims to develop a TOEFL learning model that tailored to the student’s needs. The TOEFL learning model that has been applied previously in the Indonesian Railway Polytechnic is still conventional, thus impacting students' learning interest in learning TOEFL. Therefore, a website-based TOEFL learning development model is needed to be developed. This research uses research and development (R&D) method, which is to develop and test a product. The development of this website-based TOEFL learning model uses a research and development approach ( R &D) through 3 stages, namely: 1) preliminary study, 2) development, and 3) final product. Research result showed that this application-based TOEFL learning model can increase students' interest and motivation, because this development model can provide convenience for students, especially for TOEFL learning. Therefore, after conducting feasibility trials with model experts and users, it was found that 87.7% of these models are very feasible in the implementation in the Indonesian Railway Polytechnic. The application of this web-based learning model can also increase students' learning interest, as evidenced by the results of a questionnaire on students stating that 68% of students are very interested in using this model, 22% of students are interested and 10% are not interested in using application-based learning models